Pet ownership and children's self-esteem in the context of war - Keresteš, Gordana (1998)
Development of children's self-esteem, i.e. their evaluations of themselves, is to a large extent influenced by the behavior and reactions of significant others. Research on human-animal relationship has shown that pets can serve as significant others for children as well as for adults. Several studies have found significant relationship between children's self-esteem and pet ownership in normal, peaceful circumstances. The aim of the present study was to examine whether pet ownership is related to self esteem in the context of war. The sample consisted of 612 elementary school children (301 boys, 311 girls) from Slavonia, one of the Croatian regions severely affected by the war. They were aged 11 to 14 years (5th to 8th grade). There were 439 pet-owners (295 owners of cats or dogs and 144 owners of other kinds of animals) and 173 non pet-owners. As a part of broader test battery, all children filled out Rosenberg's Self-Esteem Scale (1965). The data were analysed by means of 3 (pet ownership: non owners / owners of dogs and cats / owners of other animals) × 2 (gender) × 2 (age: 5-6 / 7-8 grade) analysis of variance (ANOVA), with results on the Self-Esteem Scale as the dependent measure. ANOVA revealed no significant main effect of pet ownership, and no significant interactions between pet-ownership and children's age and gender. The only significant effect found was the main effect of age (F=24.09, p<0.001), with younger students having higher results on the Self-Esteem Scale. The results of this preliminary study thus indicate that pet ownership is not related to children's self-esteem in the context of war.
Projekt MZOS
ENG